Simultaneous Price and Quantity Adjustment in a Single Market - Beckmann, Martin J.; Ryder, Harl E. (Econometrica, 1969)
This paper discusses the dynamics of disequilibrium in a single market where both price and quantity change in response to disequilibrium. We describe the nature of the adjustment path under a wide variety of assumptions, noting in particular the properties of stability in the large and in the small and the existence of limit cycles.